Herbivore damage and riparian shade constrain biomass distribution in American water willow (Justicia americana) - Lopez, Jonathan W.; Vaughn, Caryn C. (Aquatic botany, 2023)
Emergent macrophytes can create important linkages between aquatic and terrestrial ecosystems. American water willow (Justicia americana) is an ecological engineer that provides structure and takes up nutrients in aquatic habitats but is subject to herbivory by terrestrial animals. Here, potential constraints that terrestrial herbivory, riparian shading, porewater nutrient stoichiometry, and co-occurrence with freshwater mussels may have on standing crops of aboveground and belowground water willow biomass were investigated across nine study sites in the Kiamichi River catchment, Oklahoma, USA. Stem damage – used to indirectly assess herbivore effects – and riparian shading were both associated with significant reductions in aboveground biomass. However, these variables were also somewhat correlated with each other, suggesting a possible interaction between shade and herbivory. Belowground biomass was more variable between sites than aboveground biomass, but the environmental variables that were sampled failed to explain this variation consistently. Because shadier water willow patches tend to have nutrient-richer tissues, we suggest that the correlation between riparian shade and herbivore damage may result from selective feeding by terrestrial herbivores at shadier sites. However, further experimental work (e.g., using grazing exclosures) is needed to assess this possibility due to the limitations of using stem damage counts as an indirect representation of herbivory. Despite these limitations, the present study complements a growing body of evidence that shows emergent macrophytes are seemingly more important as a resource for herbivores than historically recognized. Emergent macrophytes may be especially important when consumed by terrestrial herbivores that then transfer aquatic-derived resources into the terrestrial habitat. The data used to generate this manuscript are available from the corresponding author upon reasonable request. •Water willow (Justicia americana) biomass crops depend on environmental conditions.•Belowground biomass standing crops are larger and more variable than aboveground.•Aboveground biomass decreases with herbivore-induced damage and shading.•Stem damage and riparian shade were positively correlated.•Shaded macrophyte beds may have higher herbivory rates, limiting standing biomass.